Electroforesis of Whey and Stretching Water Protein of Mozzarella Cheese Production from Factorial Experimental of Coagulation and Stretching Temperature - Purwadi Purwadi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2010)
The use of lime juice as acidifier in the making of Mozzarella cheese was aimed to learn the protein profile of whey and stretching water produced with treatment of coagulation and stretching temperature. The treatment of coagulation temperature was G1 = 30oC, G2 = 35oC, G3 = 40oC, and G4 = 45oC, and the treatment of stretching temperature was M1 = 70oC, M2 = 75oC, M3 = 80oC, and M4 = 85oC. The research result showed that coagulation temperature of 30 and 35 oC gave the same protein profile of whey as well as coagulation temperature of 40 and 45oC, while coagulation temperature of 30 and 35oC with coagulation temperatur of 40 and 45oC gave different protein profile of whey. Different coagulation temperature gave different protein profile of whey and stretching water, while different stretching temperature gave the same protein profile of stretching water. Coagulation temperature of 30 and 35oC gave the same protein profile of stretching water as well as coagulation temperature of 40 and 45oC, while coagulation temperature of 30 and 35oC with temperature of 40 and 45oC gave different protein profile of stretching water. Keywords: protein profile, Mozzarella cheese, coagulation temperature, stretching temperature